Risk factors and strategies for integrated management of bird pests affecting maize establishment. (October 2021) - Furlan, Lorenzo; Contiero, Barbara; Chiarini, Francesca; Bottazzo, Michele; Milosavljević, Ivan
Abstract: Bird damage to maize crops is an important cause of economic loss for maize growers in Italy. Consequently, the objectives of this study were to identify main species of birds attacking maize in north-eastern Italy and quantify the effects of agronomic characteristics, cultivation practices, landscape variables, and management practices on the incidence of bird damage to maize at establishment. A systematic survey of 5065 ha of maize cultivated land ( Zea mays L.) at early plant stages was performed from 1986 to 2020, resulting in a dataset of 1619 records. Corvids ( Corvus cornix ) were found to be the main culprits of damage to maize fields. A multifactorial model was applied to assess the impact of potential risk factors. The presence of nearby roosting areas, such as hedgerows and woodlands with trees higher than 7 m, was associated with a five-fold increased risk of damage by birds. No-tillage soil management was associated with a higher risk of bird damage when compared with minimum tillage and conventional tillage systems. The probability of damage to a field with no risk factors was always low (<1%). The application of naturally derived bird repellents incorporated in seed coatings (i.e., ScudoSeed® and Eurodif®) decreased the risk of damage to maize by birds below the threshold value of 15%, yet they were slightly outperformed by their synthetic counterparts (i.e., Methiocarb and Ziram). Our results further suggest that it is possible to implement IPM principles for pest birds in maize. Highlights: The risk of bird damage to maize at establishment increased with the presence of bordering roosting areas (woody species). No-tillage systems were associated with an increased risk of bird damage to early growth of maize. Bird repellents reduced the risk of bird damage to maize below 15%. Over a 35-yr study period, the overall risk of economic damage to early growth of maize by birds was low (<1%).